Effect of moisturizing treatments on germination of Vitex pubescens seeds - Sriwardani, F.; Budhi, S.; Kusmina, S.; Utama, R.; Rantan, D.; Jong, W. de (1998)
From the results it appears that the germination capacity is increased significantly as as result of the two treatments. The treatment soaking seeds in boiling water for 15 seconds had the best results, but these were not significantly different from the other treatment, soaking the seeds 24 hours in room-temperature water. There was, however, a difference between the response of the V.pubescens seeds to the two treatments in terms of germination rate. The different from the control treatment, whereas the difference between the control and soaking seeds in boiling water results in a very significant difference. In summary, the two treatments appear to have the same effect on the increment of the germination capacity of V.pubescens seeds. Both treatments also have a positive effect on the rate with which seeds germinate, but soaking the seeds in boiling water has a greater effect than soaking seeds in room-temperature water. Subjecting V. pubescens to any of these treatments significantly increaces the success rate of germination and the speed with which the seeds germinate. The treatment of soaking seeds for 15 seconds in boiling water is slightly more effective than soaking the seeds for 24 hours in room water